2020
DOI: 10.1186/s12951-020-00718-y
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and application of magnetic@layered double hydroxide as an anti-inflammatory drugs nanocarrier

Abstract: Background Magnetic nanocomposites with a core–shell nanostructure have huge applications in different sciences especially in the release of the drugs, because of their exclusive physical and chemical properties. In this research, magnetic@layered double hydroxide multicore@shell nanostructure was synthesized by the facile experiment and is used as novel drug nanocarrier. Methods Magnetic nanospheres were synthesized by a facile one-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Novel nanomaterials are being developed to improve disease treatment processes via biopharmaceutical molecules as well as the surface treatment of biomaterials [ 8 9 ]. Among nanoparticles (NPs), silver nanoparticles (Ag-NPs) are successfully commercialized due to their well-known antiseptic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Novel nanomaterials are being developed to improve disease treatment processes via biopharmaceutical molecules as well as the surface treatment of biomaterials [ 8 9 ]. Among nanoparticles (NPs), silver nanoparticles (Ag-NPs) are successfully commercialized due to their well-known antiseptic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the higher accumulated release reported by these authors (60%), the release profile observed in our work was more homogeneous, without the presence of burst effect and able to maintain a gradual and sustained release for more than 24 h. Compared to other polymeric nanostructured delivery systems for diclofenac, the CGP-PPG@diclofenac presented a performance similar to those from Yahia et al [ 16 ] and Duarte Junior et al [ 20 ], thus confirming the capacity of chitosan particles loaded with diclofenac sodium to provide a sustained release of this drug. Similarly, Yousefi et al [ 58 ] showed that magnetic@layered double hydroxide multicore@shell nanostructures were effective as controlled delivery systems for diclofenac and ibuprofen.…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial mechanism of the formed nanostructure mainly can be involves the electrostatic interactions of cationic and metallic parts (imidazolium units and silver NPs) with the negatively charged bacterial membrane [39,40]. However, the hydrophobic part of the nanostructure (PILP) also plays a role in the mechanism and affects the internal and hydrophobic regions of the bacteria that this helps to rupture the cell membrane[41].…”
Section: Antibacterial Activity Of Pilp-ag Organic-inorganic Nanocompositementioning
confidence: 99%